1-[-3+6+1-[4-(6-3+1)-2]
Respuestas a la pregunta
Contestado por
0
Respuesta:
El resultado es -5
Explicación paso a paso:
1-[-3+6+1-[4-(6-3+1)-2]
1-(-3+6+1-[4-(6-3+1)-2]
1-(-3+6+1-(-2)
1-6
1
-5
Contestado por
1
Explicación paso a paso:
1 - [ -3 + 6 + 1 - [ 4 - (6 - 3 + 1) - 2 ]
- (6 - 3 + 1) = 4
1 - [ -3 + 6 + 1 - [ 4 - 4 - 2 ] ]
- [ 4 - 4 - 2 ] = -2
1 - [ -3 + 6 + 1 - [-2] ]
- - [-2] = 2
1 - [ -3 + 6 + 1 + 2 ]
- [ -3 + 6 + 1 + 2 ] = 6
1 - [ 6 ]
- 1 - 6 = -5
Espero haberte ayudado y suerte!!! :)
Otras preguntas
Biología,
hace 6 meses
Informática,
hace 6 meses
Castellano,
hace 11 meses
Matemáticas,
hace 11 meses
Arte,
hace 1 año